Complete plastid genome of two Dalbergia species (Fabaceae), and their significance in conservation and phylogeny. Issue 2 (2nd April 2020) - Win, Pyae Pyae; Li, Xin; Chen, Li-Qiong; Tan, Yun-Hong; Yu, Wen-Bin
Abstract: Dalbergia (Fabaceae) is a pantropical genus. Due to high economic and ecological values, many Dalbergia species were assessed as threatened taxa. In this study, we reported the complete plastome of two Dalbergia species, D. odorifera and D. oliveri, that was 155, 838 bp and 156, 074 bp in size, respectively. Comparative analyses showed Dalbergia plastomes were conserved in genome size, structure, and gene contents. Four nucleotide diversity hotspots of Dalbergia genomes were rpl32-ndhF, rpl32-trnL UAG, trnL UAA, and trnT ACA - trnL UAA . Phylogenetic analysis revealed the sister relationship between D. odorifera and D. hainanensis, and between D. oliveri and D. assamica, respectively. The complete plastomes can provide the important information for investigations on conservation genetics and phylogenies of Dalbergia and Fabaceae.